About Engagement ("Sponsalia"). From "Jus Romanum" to "Jus Civile" of Romania - Mititelu, Cătălina (Technium Social Sciences Journal, 2022)
So far, in the Romanian specialized literature, we notice few and inconsistent papers on engagement, hence the precariousness of the studies on the legal status of the two forms of engagement, civil and religious. Therefore, in the pages of our paper we have chosen to present this legal institution both in terms of the legislation and the doctrine of (Old and New) Roman Law, and of "Jus civile" (civil law) and "Jus nomocanonicum" (ecclesiastical law), i.e., The (Byzantine) state law, whose Collections of Laws reserved a special place not only to the institution of civil engagement, but also to the religious one. This approach to our first-hand documentary research in both laws (utriusque juris), i.e., civil and religious, has given us the opportunity to give some considerations and make pertinent assessments regarding some Latin and Greek legislative texts, out of the desire to provide readers with a reference study on both forms of engagement, i.e., civil and religious.